2018
DOI: 10.1186/s12885-018-4580-6
|View full text |Cite
|
Sign up to set email alerts
|

WDR5 supports colon cancer cells by promoting methylation of H3K4 and suppressing DNA damage

Abstract: BackgroundKMT2/MLL proteins are commonly overexpressed or mutated in cancer and have been shown to support cancer maintenance. These proteins are responsible for methylating histone 3 at lysine 4 and promoting transcription and DNA synthesis; however, they are inactive outside of a multi-protein complex that requires WDR5. WDR5 has been implicated in cancer for its role in the COMPASS complex and its interaction with Myc; however, the role of WDR5 in colon cancer has not yet been elucidated.MethodsWDR5 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Early formation of neuroblastoma. In breast cancer, WDR5 has been reported to promote breast cancer proliferation through CBX8 interaction activation of the Notch pathway (Neilsen et al, 2018). WDR5 expression levels are associated with poor prognosis in breast cancer patients (Dai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Early formation of neuroblastoma. In breast cancer, WDR5 has been reported to promote breast cancer proliferation through CBX8 interaction activation of the Notch pathway (Neilsen et al, 2018). WDR5 expression levels are associated with poor prognosis in breast cancer patients (Dai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, both WDR5 and DPY30 depletion display an opposite phenotype as the one observed upon ASH2L knockdown. Down-regulation of WDR5 in colorectal cancer induces DNA damage and chemosensitivity (55), and knockdown of DPY30 increases the levels of endogenous DNA damage and decrease the DNA repair ability of hematopoietic stem cells (56). What seems to stand out about ASH2L is that it is the only core member of the methyl-transferase complexes that is required for the addition of the third methyl group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that WDR5 plays key roles in the tumorigenesis and progression of a variety of cancers ( 34 , 35 , 44 , 55 60 ). Myc family oncoproteins are among the most prevalent oncogenic transcription factors, and c-Myc and N-Myc induce tumorigenesis by regulating gene transcription in human cancer tissues of various organ origins ( 34 , 35 , 55 ).…”
Section: The Role Of Wdr5 In Cancermentioning
confidence: 99%
“…WDR5 is over-expressed in gastric and colon cancer cell lines and human tumor tissues, and high levels of WDR5 expression in tumor tissues is associated with poor patient survival rate ( 59 , 60 ). Mechanistically, in gastric cancer cells, WDR5 induces histone H3K4 trimethylation at the Cyclin D1 gene promoter and Cyclin D1 gene transcription, leading to cancer cell proliferation ( 59 ).…”
Section: The Role Of Wdr5 In Cancermentioning
confidence: 99%
See 1 more Smart Citation